The Study of Eco Enzymes Application For Decoloring Textile Industry Wastewater Following by pH Value Analysis - Annisa Rahma Anindita; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2023)
Abstract. There is a good potential between the increase in the growth of the textile industry, especially on a small scale which also causes a lot of environmental pollution of colored water in the water bodies of the area around the textile industry With the great potential of using Eco Enzyme which can be used as a biocatalyst. Eco Enzyme contains several types of enzymes, which can be used as tools to speed up the textile wastewater decoloring process which is included in the Biological method in textile wastewater treatment. Objective. To find out what are the results of color removal efficiency after adding by Eco Enzymes, and its effect on the pH values. Methods and Results. In this research, by using 10% concentration from Orange and Dragon Fruit Peels. The sample that was added by Orange Eco Enzymes (OEE) and Dragon Fruit Eco Enzymes (DEE) has a color removal respectively in 80% and 82% in 48h then continuously slowly degrades slowly to 86% and 86% in 120h. Before adding the Eco Enzyme, the sample has a high pH of 10.98. After added by OEE and DEE, in 48h respectively the pH values decrease to 9.58 and 8.98, then continuously slowly degrades to 8.70 and 8.56 in 120h. Conclusion. The results show that selected Eco Enzymes are able to decolor textile wastewater also following by reducing pH and already stable starts from 48h.